Extracorporeal Cardiopulmonary Resuscitation—Where Do We Currently Stand? - Brandon E. Ferrell; Jason Thomas; John P. Skendelas; Mayuko Uehara; Tadahisa Sugiura (Biomedicines)
Extracorporeal cardiopulmonary resuscitation (eCPR) is a method of acute resuscitation for patients who have suffered a cardiac arrest through the utilization of an extracorporeal membrane oxygenation (ECMO) pump. The use and efficacy of eCPR is an active area of investigation with ongoing clinical investigation across the world. Since its inception, ECMO has been utilized for several conditions, but more recently, its efficacy in maintaining cerebrovascular perfusion in eCPR has generated interest in more widespread utilization, particularly in cases of out-of-hospital cardiac arrest. However, successful implementation of eCPR can be technically challenging and resource intensive and has been countered with ethical challenges beyond the scope of conventional in-hospital ECMO care. The aim of this review is to summarize the status of eCPR in the current era.